Basic Jarimatika is a Multiplication Solution in Learning in the Merdeka Curriculum for Preservice Elementary Teacher - Hanifah, Maria; Nurjani, Nurjani; Adlani, Nazri (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Multiplication in Mathematics lessons is a problem for elementary school students. Basic math is the solution to this multiplication problem. Basic Jarimatika is a method that uses the fingers of the hand to solve students' problems in calculating based on the rules of hand formation and the solution of Jarimamatics. This research aims to 1) find out preservice elementary teachers' responses after learning Jarimatika, and 2) provide an overview of the need for using Jarimatika media in the preservice elementary teacher curriculum. The research method used is mixed. The type of mix-method method used is concurrent embedded (a mixture of reinforcement where quantitative methods strengthen qualitative methods. The instruments used are structured interview instruments and open questionnaires. The results of this study provide an illustration that basic mathematics is given a good category in the analysis of the questionnaire obtained. This good category is strengthened by the interview media which gives the researcher the impression that students feel it is quite helpful in using Jarimatika to deepen the learning of multiplication basic multiplication at the elementary/MI level.